Breath Methane Does Not Correlate With Constipation Severity or Bloating in Patients With Constipation. Issue 4 (April 2020) - Singh, Prashant; Duehren, Sarah; Katon, Jesse; Rangan, Vikram; Ballou, Sarah; Patel, Raxitkumar; Iturrino, Johanna; Lembo, Anthony; Nee, Judy
Abstract : Goals: We aimed to study (1) if the breath methane level on glucose breath testing (GBT) was associated with constipation severity and (2) compare methane levels between patients with constipation and diarrhea. Background: The breath methane level has been associated with constipation and its severity. However, a few recent studies have questioned these associations. Study: Patients presenting consecutively to a tertiary care gastroenterology motility laboratory for GBT were included. GBT was performed using 75-g glucose load following a standard, institutional protocol. Constipation and irritable bowel syndrome (IBS) severity was measured using Patient Assessment of Constipation Symptoms (PAC-SYM) and IBS-symptom severity scale (IBS-SSS). Results: In the cohort of 79 constipated patients, there was no significant correlation between baseline or maximum methane levels with total PAC-SYM score. IBS-SSS or bloating severity also did not correlate with baseline or maximum methane levels. The baseline or maximum methane levels of ≥3 and 5 ppm were equally distributed among those with constipation (n=79) and diarrhea (n=122). Only baseline methane levels of ≥10 and ≥20 ppm significantly correlated with constipation ( P <0.001 for both). Conclusions: We found that constipation and bloating severity did not correlate with methane levels on GBT. In addition, only higher baseline methane levels (≥10 and ≥20 ppm) significantly correlated with constipation as baseline methane levels up to 5 ppm were equally common in patients with diarrhea and constipation. Baseline methane levels had better correlation with constipation compared with maximum levels of methane achieved.